2017
DOI: 10.1039/c7ra06844a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cellular uptake of iron oxide nanoparticles modified with 1,2-dimyristoyl-sn-glycero-3-phosphocholine

Abstract: DMPC greatly enhanced the cellular uptake of SPIONs, resulting in remarkable amounts of accumulated nanoparticles in PC-12 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
(38 reference statements)
2
8
0
Order By: Relevance
“…ICP-OES demonstrated that an average of 12.8 ± 3.6 pg Fe was internalised into each cell (with 12.8 pg Fe equating to 16,487 nanoparticles) and subsequent Prussian blue staining confirmed this internalisation and identified the nanoparticles propensity to accumulate around the nuclear membrane. This level of iron uptake into cells is comparable to the results reported from similar protocols published previously [35][36][37]. Next, intracellular hyperthermia, extracellular hyperthermia, and intracellular and extracellular hyperthermia were compared to define differences in viability through Annexin V/7-AAD staining.…”
Section: Discussionsupporting
confidence: 83%
“…ICP-OES demonstrated that an average of 12.8 ± 3.6 pg Fe was internalised into each cell (with 12.8 pg Fe equating to 16,487 nanoparticles) and subsequent Prussian blue staining confirmed this internalisation and identified the nanoparticles propensity to accumulate around the nuclear membrane. This level of iron uptake into cells is comparable to the results reported from similar protocols published previously [35][36][37]. Next, intracellular hyperthermia, extracellular hyperthermia, and intracellular and extracellular hyperthermia were compared to define differences in viability through Annexin V/7-AAD staining.…”
Section: Discussionsupporting
confidence: 83%
“…In our previous work, we tried to modify the surface of nanoparticles with DMPC (1,2-dimyristoyl- sn -glycero-3-phos-phocholine) and GSH (glutathione), but severe endocytosis of the nanoparticles occurred after their injection into the substantia nigra. , In this study, we examine CS surface modification to achieve extracellular distribution of nanoparticles, because CS is commonly found on the cell membrane. There are many CS receptors in cell membranes, such as CD-44, TLR4 (toll-like receptor 4), and intercellular bonding molecules, which would attach CS to the cell membrane, and CS becomes a component of the neural network system .…”
Section: Resultsmentioning
confidence: 99%
“…The raw materials used and the synthesis of PEI-PEG-SPIONs (PEG: poly­(ethylene) glycol, PEI: polyethylene imine) are as previously reported. , 0.3 g of PEI was dissolved in 15 g of PEG at 80 °C with vigorous magnetic stirring in a three-neck round-bottom flask for 10 min, and then 0.7 g of Fe­(acac) 3 was added to the flask with stirring for another 10 min. This red solution was heated to 260 °C at a rate of 7.2 °C/min under a flow of argon and held at that temperature for 1 h. The reactants were cooled to 60 °C by removing the heat source and then mixed with 60 mL of toluene; after ultrasonic stirring, the particles were precipitated by the adsorption of magnet and washed twice with acetone to remove the excess organics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer‐based surface coatings yield effective steric stabilization of the iron surfaces and prevent aggregation of particles [ 20b ] and are the most typical approach. Passivating SPIOs with PVP, [ 155 ] polyglycerol adipate, [ 156 ] or polyethyleneimine (PEI) [ 157 ] via either in situ or ex situ synthetic processes are commonly reported. In particular, the primary amine groups present in PEI molecule enable their conjugation with tumor‐targeting molecules or other functional molecules.…”
Section: Metal‐based Mri Contrast Agentsmentioning
confidence: 99%